2023
DOI: 10.25258/ijpqa.14.1.11
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro Anticancer Activity of Various Plant Extracts

Abstract: Herbal medicinal plants have been explored for a variety of pharmacological properties but still a large number of phytoconstituents are still unexplored. The manuscript aims to assess the anticancer property of Leucas cephalotes (Roth) Spreng, Acalypha indica L. and Lantana camara L. extracts on MDA-MB-231, A-549, PC-3 and Hep-G2 cell lines. The ethanol extract of the selected plants was explored for anticancer activity by SRB assay. Since L. camara exhibited promising activity, this plant’s successive extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Ramkumar et al reported cytotoxic properties of L. camara root extract-derived gold nanoparticles on MDA-MB-231 cells (Ramkumar et al, 2017) and in a recent study, El-Din et al showed that methanolic extract of L. camara leaves could exert cytotoxic effect on several cancer cell lines including MCF-7 and MDA-MB-231 breast cancer cells; however, the mechanism of cytotoxicity in breast cancer cell lines was not investigated (El-Din et al, 2022). More recently, Mishra et al reported that extracts of the whole Lantana camara plant harbours cytotoxic effect against triple negative MDA-MB-231 cells although the mechanism of cytotoxicity was unexplored for this cell line (Mishra et al, 2023). It is therefore important to explore the mode of cytotoxic action of Lantana camara leaf extract on breast cancer cell lines, particularly on the triple negative breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Ramkumar et al reported cytotoxic properties of L. camara root extract-derived gold nanoparticles on MDA-MB-231 cells (Ramkumar et al, 2017) and in a recent study, El-Din et al showed that methanolic extract of L. camara leaves could exert cytotoxic effect on several cancer cell lines including MCF-7 and MDA-MB-231 breast cancer cells; however, the mechanism of cytotoxicity in breast cancer cell lines was not investigated (El-Din et al, 2022). More recently, Mishra et al reported that extracts of the whole Lantana camara plant harbours cytotoxic effect against triple negative MDA-MB-231 cells although the mechanism of cytotoxicity was unexplored for this cell line (Mishra et al, 2023). It is therefore important to explore the mode of cytotoxic action of Lantana camara leaf extract on breast cancer cell lines, particularly on the triple negative breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%